Ruin Considerations and Debt Issuance - Bierman, Harold; Thomas, L. Joseph (Journal of Financial and Quantitative Analysis, 1972)
The current literature or business finance states that debt is a cheaper source of capital than stock (tending to reduce the firm's cost of capital), because interest is deductible for income tax purposes while the return to common stockholders is subject to tax. It is even possible to issue debt without increasing the risk to the owners (the debt is issued to stockholders in proportion to the ownership of stock, or equivalently investors buy a mixture of stocks and bonds on the market). However, it is argued in this paper that if we assume that the present stockholders have no further resources available for investment in the firm, but the enterprise needs additional resources, then the present stockholders have to make a basic decision about whether to issue stock or debt to raise the additional needed capital. The issuance of debt in this situation increases risk, and the issuance of stock dilutes ownership. Even when bondholders require a much lower contractual return than the expected annual return of stockholders, the issuance of more stock may be preferred to the issuance of debt.